X-ray Dose Rate and Spectral Measurements during Ultrafast Laser Machining Using a Calibrated (High-Sensitivity) Novel X-ray Detector - Mosel, Philip; Sankar, Pranitha; Düsing, Jan Friedrich; Dittmar, Günter; Püster, Thomas; Jäschke, Peter; Vahlbruch, Jan-Willem; Morgner, Uwe; Kovacev, Milutin (Materials, 2021)
Ultrashort pulse laser machining is subject to increase the processing speeds by scaling average power and pulse repetition rate, accompanied with higher dose rates of X-ray emission generated during laser–matter interaction. In particular, the X-ray energy range below 10 keV is rarely studied in a quantitative approach. We present measurements with a novel calibrated X-ray detector in the detection range of 2–20 keV and show the dependence of X-ray radiation dose rates and the spectral emissions for different laser parameters from frequently used metals, alloys, and ceramics for ultrafast laser machining. Our investigations include the dose rate dependence on various laser parameters available in ultrafast laser laboratories as well as on industrial laser systems. The measured X-ray dose rates for high repetition rate lasers with different materials definitely exceed the legal limitations in the absence of radiation shielding.